Rhizobacteria as Biocontrol Agents of Root Rot Disease on Shallot - Nunik Iriyanti Ramadhan; Hadiwiyono Hadiwiyono; Sudadi Sudadi (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2015)
Shallot is a high-economic value commodit, but so far the supply is still lower than the demand. One of the production problem is “moler” disease of shallot (MDS) caused by Fusarium oxysporum f.sp. cepae (FOCe). The aim of this research was to study the potentiality of shallot rhizobacteria (SRB) from various soil ordo to inhibit (MDS). This research was held in the Laboratory of Biology and Soil Health and Greenhouse at UNS. This research was carried out by exploring rhizobacteria of shallot planted on Entisols, Andisols, and Vertisols. Rhizobacteria exploration results were tested for their ability to control Fusarium oxysporum f.sp.cepae (FOCe). Inhibitory ability test of SRB to FOCe was carried out in vitro and on shallot in the greenhouse. The research cused a Completely Randomized Design (CDR) with two factors. The first factor was rhizobacteria combination and the second factor was various soil ordo (Andisols, Entisols, and Vertisols). Each treatment was repeated three times. It was obtained three rhizobacteria isolates from Vertisols (B15: 70%), Andisols (B12:45,55%), and Entisols (B10:46,67%) being the highest inhibition results to FOCe. The combination of rhizobacteria B12 and B10 provided the lowest intensity.